"Bohemios" e "floreados" : noite, sociabilidade e crime nos bares pelotenses (1930-1939) - Carvalho, Thaís de Freitas (2021)
This research deals with the nighttime sociability present in bars, general stores, kiosks and cafes in the city of Pelotas in the 1930s. It is assumed that these spaces constituted points of interaction between different social strata, significantly impacted by the context of densification of nightlife driven by the acceleration of electrification. The aim was to demonstrate how the insertion of the working masses in an economy in the process of diversification also promoted the propagation of ambivalent representations about the nights of drunkenness, games and fights linked to bars and widely reported by the press. Police action, close to the habits of popular classes, was sometimes confused with the informal logic that guided male disputes in these places. Without being an exclusive moment of this sociability, the night time, however, gave it unique characteristics, since it added different uses and meanings comparatively to the daytime practices in these spaces. When looking at a long-lasting habit in modern and contemporary cultures, we sought to understand how much their local configurations – situated in space and time – reveal about different dynamics of night experience present in the city, their internal confrontations and their strategies before formal justice, also going through the social imaginary that surrounded these habits.